Nöropatisi Olan Tip 2 Diyabetiklerde Yürüyüşün Ayak Taban Basıncı ve Sıcaklığı Üzerine Etkisinin İncelenmesi - Mercan, Mehtap (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
The aim of this study was to investigate the effect of gait on foot plantar pressure and temperature in type 2 diabetic individuals with neuropathy. Subjects with neuropathy (n= 44) over 18 years of age were included in the study. The presence of neuropathy was evaluated by Michigan Neuropathy Screening Instrument. Each participant visited for 3 times with at least one day intervals and walked on the treadmill for 2000 steps at first visit, 4000 step at second and 6000 steps at last. Step numbers were counted with a pedometer (Mesitaş, JP600-E) attached to the ankle. Demographic evaluation form was measured by plantar pressure analysis system (Medilogic, Germany) and plantar temperature by infrared thermometer (SABA, Germany) from 5 regions. Plantar pressure and plantar temperature measurements were repeated before and after each walk. As a result; as the number of walking steps increased, the plantar temperature of the feet increased in all regions (p<0.05). After 6000 steps, the peak pressure value increased in both feet according to 2000 steps under 1st distal metatarsal and lateral heel (p<0.05). As the T2D subjects with neuropathy have increased risk of ulcer development, they sould be carefull during walking because of the increased plantar temperature and pressure under areas with greater risk with increased steps of walking.

ÖZ: Bu çalışma nöropatisi olan tip 2 diyabetik bireylerde yürüyüşün ayak taban basıncı ve sıcaklığı üzerine etkisinin incelenmesi amacıyla gerçekleştirildi. Çalışmaya 18 yaş üstü nöropatisi olan bireyler (n=44) alındı. Nöropatinin varlığı Michigan Nöropati Tarama Enstrümanı ile değerlendirildi. Her katılımcı en az bir gün arayla 3 ziyaret yaparak, ilk geldiklerinde 2000 adım, ikinci geldiklerinde 4000 adım ve son geldiklerinde ise 6000 adım koşu bandında yürüdüler. Adım sayıları ayak bileğine takılan pedometre (Mesitaş, JP600-E) ile sayıldı. Demografik değerlendirme formu, plantar basınç analiz sistemi (Medilogic, Almanya) ile ölçülürken, plantar sıcaklık ise kızılötesi termometresi (SABA, Almanya) ile 5 bölgeden ölçüldü. Plantar basınç ve plantar sıcaklık ölçümleri her yürüyüş öncesinde ve sonrasında tekrarlandı. Sonuç olarak; yürüyüş adım sayısı arttıkça ayak taban sıcaklığı tüm bölgelerinde artış gösterdi (p<0.05). 6000 adım sonrası 2000 adıma göre her iki ayakta tepe basınç değerinin 1. metatars distali ve topuk lateralinde arttığı görüldü (p<0.05). Nöropatisi olan T2D’ler artmış ülser riskine sahip olduğu için yürüyüş yapmak istediklerinde artan adım sayısıyla birlikte ülser riski olan bölgelerde sıcaklık ve basınç artışının meydana geldiğinden hastaların dikkatli olması gerekmektedir.
Fizyoterapi ve Rehabilitasyon Dalında Yüksek Lisans Tezidir. Tez (Yüksek Lisans)--Doğu Akdeniz Üniversitesi, Sağlık Bilimleri Fakültesi, Fizyoterapi ve Rehabilitasyon Bölümü, 2019. Tez Danışmanı: Yard. Doç. Dr. Yasin Yurt
Keywords: Fizyoterapi ve Rehabilitasyon; Diyabet Hastaları--Kıbrıs (Kuzey Kıbrıs Türk Cumhuriyeti, 1983-); Tip 2 Diyabetus Mellitus; Diyabetik Ayak; Plantar Basınç; Plantar Sıcaklık; Type 2 Diabetes Mellitus; Diabetic Foot; Plantar Pressure; Plantar Temperature